Positive electrode active material for lithium secondary battery having multiphase structure and method for manufacturing same

By introducing lithium oxide with a multiphase structure into the positive electrode active material of lithium secondary battery, combined with a high-energy ball mill and heat treatment process, the problems of small capacity and poor characteristics of existing materials at high temperatures are solved, and higher energy density and cycle life are achieved.

CN119920893APending Publication Date: 2025-05-02HYUNDAI MOTOR CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410150179.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-30
Filing Date
2024-02-02
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing lithium manganese oxide positive electrode active materials exhibit problems of small capacity and poor high temperature characteristics at high temperatures.

Method used

The material is made by a lithium oxide material with a multiphase structure, including a cationic disordered rock salt (DRX) structure and spinel structure, and the material is made by a high-energy planetary ball mill and heat treatment.

Benefits of technology

It improves the energy density and cycle life of lithium secondary batteries and enhances the stability of the material at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920893A_ABST
    Figure CN119920893A_ABST
Patent Text Reader

Abstract

Disclosed herein are a positive electrode active material for a lithium secondary battery having a multiphase structure and a method of manufacturing the same. The positive electrode active material includes lithium oxide having a chemical formula of Li1 + xMn2O4 and has a multiphase structure including at least a cationic disordered rock salt (DRX) structure. In the formula, x satisfies the relationship 0 < = x < = 0.75.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material for a lithium secondary battery having a multi-phase structure and a method for manufacturing the same. Background Art

[0002] A battery is a device that stores electricity using materials that enable electrochemical reactions in positive and negative electrodes. As a representative example of a battery, a lithium secondary battery stores electrical energy using a chemical potential difference when lithium ions are intercalated and deintercalated in and from positive and negative electrodes.

[0003] Lithium oxide (Li) is used as a positive electrode active material for lithium secondary batteries. For example, LiCoO 2 、LiMn 2 O 4 、LiMnO 2 、LiNiO 2 , and nickel (Ni), cobalt (Co), manganese (Mn) or aluminum (Al) composite oxides may be used as lithium oxide.

[0004] Including LiMnO 2 、LiMn 2 O 4 Lithium manganese oxides such as MgO have advantages such as excellent thermal stability and low price, but have disadvantages such as small capacity and poor high-temperature characteristics.

[0005] The above information disclosed in this Background section is only for enhancement of understanding of the background technology of the present disclosure. Therefore, the Background section may contain information that does not form the prior art that is already known to a person of ordinary skill in the art. Summary of the invention

[0006] The present disclosure is directed to solving the above problems associated with the prior art. An object of the present disclosure is to provide a positive electrode active material for a lithium secondary battery having a multi-phase structure. Another object of the present disclosure is to provide a method for manufacturing the same.

[0007] In one aspect, the present disclosure provides a positive electrode active material for a lithium secondary battery. The positive electrode active material includes lithium oxide represented by Chemical Formula 1 and has a multi-phase structure including at least a cation disordered rocksalt (DRX) structure.

[0008] Chemical formula 1

[0009] Li 1+x Mn 2 O 4

[0010] In Chemical Formula 1, x satisfies the relationship of 0≤x≤0.75.

[0011] In one embodiment, the positive electrode active material may further include at least one of a layered structure or a spinel structure.

[0012] In another embodiment, the positive electrode active material may exhibit peaks at 2θ=19°±0.5°, 31°±0.5°, 36.5°±0.5°, 48.5°±0.5°, 55°±0.5°, 58.5°±0.5°, 67.5°±0.5°, 68.5°±0.5°, 76°±0.5°, and 84°±0.5° in X-ray diffraction analysis using CuKα radiation.

[0013] In yet another embodiment, the positive active material may exhibit peaks at 2θ=38°±0.5°, 44.5°±0.5°, 64.5°±0.5°, 77.5°±0.5°, and 81°±0.5° in X-ray diffraction analysis using CuKα radiation.

[0014] In yet another embodiment, the area (A) of the peak due to the spinel structure exhibited in X-ray diffraction analysis using CuKα radiation is 尖晶石 ) and the total area of ​​all peaks of the positive electrode active material (A 总计 ) ratio (A 尖晶石 / A 总计 ) can be in the range of 0.1 to 99.8.

[0015] In another embodiment, the area (A) of the peak due to the DRX structure presented in X-ray diffraction analysis using CuKα radiation is DRX ) and the total area of ​​all peaks of the positive electrode active material (A 总计 ) ratio (A DRX / A 总计 ) can be in the range of 0.2 to 0.99.

[0016] In other embodiments, the lithium oxide may include Li 1.25 Mn 2 O 4 .

[0017] In another embodiment, the area (A) of the peak due to the spinel structure presented in X-ray diffraction analysis using CuKα radiation is 尖晶石 ) and the total area of ​​all peaks of the positive electrode active material (A 总计 ) ratio (A 尖晶石 / A 总计 ) can be in the range of 0.4 to 0.6.

[0018] In yet another embodiment, the area (A) of the peak due to the DRX structure presented in X-ray diffraction analysis using CuKα radiation isDRX ) and the total area of ​​all peaks of the positive electrode active material (A 总计 ) ratio (A DRX / A 总计 ) can be in the range of 0.4 to 0.6.

[0019] On the other hand, the present disclosure provides a method for manufacturing a positive electrode active material for a lithium secondary battery, the positive electrode active material having a multiphase structure including at least a cationic disordered rock salt (DRX) structure. The manufacturing method includes preparing a raw material, obtaining an intermediate material by pulverizing the raw material, and obtaining a lithium oxide represented by Chemical Formula 1 by heat treating the intermediate material.

[0020] In one embodiment, when obtaining the intermediate material, the raw material may be pulverized by applying a force ranging from 10 G to 20 G to the raw material for 10 to 30 hours using a ball mill.

[0021] Other aspects and embodiments of the disclosure are discussed below.

[0022] The above and other features of the present disclosure are also discussed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The above and other features of the present disclosure are described in detail with reference to certain example embodiments of the present disclosure illustrated in the accompanying drawings, which are given hereinafter by way of illustration only and therefore do not limit the present disclosure, and in which:

[0024] Figure 1 A transmission electron microscope (TEM) image of the positive electrode active material according to Example 1 is shown;

[0025] Figure 2 shows a TEM image of a positive electrode active material according to Example 3;

[0026] Figure 3 shows a TEM image of a positive electrode active material according to Example 4;

[0027] Figure 4 shows an X-ray diffraction analysis of the positive electrode active material according to Example 1;

[0028] Figure 5 shows an X-ray diffraction analysis of the positive electrode active material according to Example 2;

[0029] Figure 6 shows an X-ray diffraction analysis of the positive electrode active material according to Example 3;

[0030] Figure 7 shows an X-ray diffraction analysis of a positive electrode active material according to Example 4;

[0031] Figure 8Capacity and cycle life evaluation of a lithium secondary battery using the positive electrode active material according to Example 1 are shown;

[0032] Fig. 9 Capacity and cycle life evaluation of a lithium secondary battery using the positive electrode active material according to Example 2 are shown;

[0033] Fig.10 shows the capacity and cycle life evaluation of a lithium secondary battery using the positive electrode active material according to Example 3; and

[0034] Fig.11 Capacity and cycle life evaluation of a lithium secondary battery using the positive electrode active material according to Example 4 are shown.

[0035] It should be understood that the accompanying drawings are not necessarily shown or drawn to scale, presenting a somewhat simplified representation of various features illustrating the basic principles of the present disclosure. The specific design features of the present disclosure as disclosed herein, including, for example, specific dimensions, orientations, locations, and shapes, will be determined in part by the specific intended application and use environment.

[0036] In the drawings, like reference numerals refer to the same or equivalent parts of the present disclosure throughout the several figures of the drawing. DETAILED DESCRIPTION

[0037] From the description of the embodiments given below with reference to the accompanying drawings, the above-mentioned objects, other objects, advantages and features of the present disclosure will become apparent. However, the present disclosure is not limited to the embodiments disclosed herein and can be implemented in various different forms. The embodiments are provided to make the description of the present disclosure thorough and to fully convey the scope of the present disclosure to those of ordinary skill in the art.

[0038] In the accompanying drawings, the same or similar elements are represented by the same reference numerals, even if they are depicted in different drawings. In the accompanying drawings, for clarity of description, the size of the structure may be enlarged compared to its actual size. In the following description of the embodiment, terms such as "first" and "second" may be used to describe various elements, but these elements are not limited. These terms are only used to distinguish an element from other elements. For example, without departing from the scope and spirit of the present disclosure, the first element may be named as the second element, and similarly, the second element may be named as the first element. Singular expressions may encompass plural expressions unless they have significantly different contextual meanings.

[0039] In the description of the following embodiments, terms such as "comprise", "include" and "have" should be interpreted as indicating the presence of features, numbers, steps, operations, elements or components or combinations thereof stated in the specification. Such terms do not exclude the presence of one or more other features, numbers, steps, operations, elements, components, or combinations thereof or the possibility of adding them. In addition, it should be understood that when a component such as a layer, film, region or plate is referred to as being "above" another component, the component may be "directly" located "above" the other component, or other components may be inserted between the two components. In the same way, it should be understood that when a component such as a layer, film, region or plate is referred to as being "below" another component, the component may be "directly" located "below" the other component, or other components may be inserted between the two components.

[0040] All numerals, values ​​and / or expressions of the amount of components, reaction conditions, polymer compositions and blends used in the specification are approximate values, which reflect the various uncertainties in the measurements produced when these values ​​are obtained from essentially different things. Therefore, it should be understood that these numerals, values ​​and / or expressions are modified by the term "about", unless otherwise stated. In addition, it should be understood that if a numerical range is disclosed in the specification, such ranges include all continuous values ​​from the minimum value of the range to the maximum value, unless otherwise stated. In addition, if such ranges refer to integers, such ranges include all integers from the minimum integer to the maximum integer, unless otherwise stated.

[0041] The positive active material according to the present disclosure may include lithium oxide represented by the following Chemical Formula 1.

[0042] Chemical formula 1

[0043] Li 1+x Mn 2 O 4

[0044] In Chemical Formula 1, x may satisfy the relationship of 0≤x≤0.75.

[0045] The positive electrode active material may have a multiphase structure including at least a cationic disordered rock salt (DRX) structure. The positive electrode active material may also include at least one of a layered structure or a spinel structure.

[0046] The cation disordered rock salt (DRX) structure is a structure in which large anions are most densely stacked and all holes in the octahedron are filled with cations. The cation disordered rock salt (DRX) structure has a smaller electrical repulsion than the layered structure provided by anions and cations alternately and is therefore very stable. Therefore, the positive electrode active material with the cation disordered rock salt (DRX) structure can undergo very small volume changes during charging and discharging, and can enable lithium ions to be intercalated and deintercalated by a mechanism similar to that of Li-rich oxides.

[0047] The spinel structure forms an octahedron of oxygen ions similar to a layered structure, and transition metal ions exist therein. Lithium ions and transition metal ions occupy tetrahedral (8a) and octahedral (16d) positions, respectively. Due to such structural characteristics, the spinel structure has a three-dimensional lithium ion diffusion path. Lithium ions can thus be inserted into the spinel structure in various directions.

[0048] In the layered structure, MO 2 The structure (where M represents a metal) is formed by alternating layers of lithium ions. 2 In the structure, octahedrons with transition metal ions occupying their centers and oxygen ions occupying their vertices share corners with each other. The layered structure has a two-dimensional lithium ion diffusion path and thus has a high diffusion rate. In addition, the layered structure has a wide storage space for lithium ions and thus exhibits a high theoretical capacity.

[0049] When x indicating the molar number of lithium atoms in Chemical Formula 1 changes, the phase ratio of the positive electrode active material may change. When a positive electrode active material having an appropriate phase ratio is used, the energy density, cycle life, etc. of a lithium secondary battery including the positive electrode active material may be improved. This will be described below with reference to an embodiment.

[0050] The lithium manganese oxide having a multi-phase structure according to the present disclosure cannot be manufactured by a simple pulverization and calcination process. The manufacturing method of the positive electrode active material for a lithium secondary battery according to the present disclosure may include preparing a raw material, obtaining an intermediate material by pulverizing the raw material using a high-energy planetary ball mill, and obtaining lithium oxide represented by the above chemical formula 1 by heat treating the intermediate material.

[0051] The raw materials may include a lithium precursor, a manganese precursor, and the like.

[0052] The lithium precursor is not limited to a specific substance, and may include, for example, Li 2 O、LiCO 3 、LiNO 3 , Li 3 N, LiF, LiS, LiI, etc.

[0053] The manganese precursor is not limited to a specific substance and may include, for example, MnO2 , Mn 2 O 3 , Mn 3 O 4 wait.

[0054] The raw materials may be weighed to suit the desired composition of lithium oxide and the preparation may be carried out.

[0055] Thereafter, the intermediate material can be obtained by pulverizing the raw material using a high-energy planetary ball mill instead of a common ball mill.

[0056] As the high-energy planetary ball mill, any commercially available device can be used. For example, a device called PM200 produced by RETSCH can be used.

[0057] When obtaining the intermediate material, the raw material can be crushed by applying a force in the range of 10G to 22G, or in the range of 17G to 22G, to the raw material using a high-energy planetary ball mill for 10 to 30 hours or 25 to 30 hours. Only when the above-mentioned force and time range for the raw material are met, a positive electrode active material having a multiphase structure can be manufactured.

[0058] Lithium oxide can be obtained by heat treating the intermediate material. The heat treatment method and conditions are not limited to specific methods and conditions. Any method and conditions commonly used in the technical field to which the present disclosure belongs can be performed. For example, the heat treatment can be performed by placing the intermediate material in a furnace and then heating the intermediate material, or by applying microwaves to the intermediate material.

[0059] Hereinafter, the present disclosure is described in more detail by the following examples. The following examples are only used to describe the present disclosure by way of example and are not intended to limit the scope and spirit of the present disclosure.

[0060] Example 1

[0061] Made of LiMn 2 O 4 The raw material is prepared by weighing the lithium precursor and the manganese precursor to adapt to the composition. A high-energy planetary ball mill (PM200 produced by Lach Company) is driven at about 450 rpm to apply a force of about 17.77 G to the raw material for about 25 hours. The lithium oxide is obtained by heat treating the intermediate material thus obtained.

[0062] Example 2

[0063] Manufacturing is represented by Li 1.25 Mn 2 O 4 The raw material was prepared by weighing the lithium precursor and the manganese precursor to suit the composition. Thereafter, lithium oxide was manufactured by the same method and conditions as in Example 1.

[0064] Example 3

[0065] Manufacturing is represented by Li 1.5 Mn 2 O 4 The raw material was prepared by weighing the lithium precursor and the manganese precursor to suit the composition. Thereafter, lithium oxide was manufactured by the same method and conditions as in Example 1.

[0066] Example 4

[0067] Manufacturing is represented by Li 1.75 Mn 2 O 4 The raw material was prepared by weighing the lithium precursor and the manganese precursor to suit the composition. Thereafter, lithium oxide was manufactured by the same method and conditions as in Example 1.

[0068] Figure 1 A transmission electron microscope (TEM) image of the positive electrode active material according to Example 1 is shown. Figure 2 A TEM image of the positive electrode active material according to Example 3 is shown. Figure 3 A TEM image of the positive electrode active material according to Example 4 is shown.

[0069] refer to Figure 1-3 , in the positive electrode active material according to the present disclosure, all of the layered structure, the spinel structure, and the DRX structure appear.

[0070] Figure 4 X-ray diffraction analysis of the positive electrode active material according to Example 1 is shown. Figure 5 X-ray diffraction analysis of the positive electrode active material according to Example 2 is shown. Figure 6 X-ray diffraction analysis of the positive electrode active material according to Example 3 is shown. Figure 7 X-ray diffraction analysis of the positive electrode active material according to Example 4 is shown.

[0071] refer to Figure 4-6 , the positive electrode active materials according to Examples 1-3 exhibited a peak due to the DRX structure and a peak due to the spinel structure.

[0072] The positive active material according to the present disclosure exhibits peaks at 2θ=19°±0.5°, 31°±0.5°, 36.5°±0.5°, 48.5°±0.5°, 55°±0.5°, 58.5°±0.5°, 67.5°±0.5°, 68.5°±0.5°, 76°±0.5° and 84°±0.5° in X-ray diffraction analysis using CuKα radiation. These peaks are due to the formation of spinel structure.

[0073] In addition, the positive active material according to the present disclosure exhibits peaks at 2θ=38°±0.5°, 44.5°±0.5°, 64.5°±0.5°, 77.5°±0.5°, and 81°±0.5° in X-ray diffraction analysis using CuKα radiation. These peaks are formed due to the DRX structure.

[0074] refer to Figure 7 , the positive electrode active material according to Example 4 does not present a peak due to the spinel structure. However, due to the fact that the spinel phase is partially formed in the DRX structure as the x value increases, the result of Example 4 is obtained. Therefore, it is not that the spinel phase does not exist in the positive electrode active material according to Example 4.

[0075] The area ratio of each peak is based on Figure 4-7 The results are calculated and listed in Table 1.

[0076] Table 1

[0077] category composition <![CDATA[A DRX / A 总计 1) ]]> <![CDATA[A 尖晶石 / A 总计 2) ]]> Example 1 <![CDATA[LiMn 2 THE 4 ]]> 0.2 99.8 Example 2 <![CDATA[Li 1.25 Mn 2 ABOUT 4 ]]> 52.4 47.6 Example 3 <![CDATA[Li 1.5 Mn 2 ABOUT 4 ]]> 90 10 Example 4 <![CDATA[Li 1.75 Mn 2 ABOUT 4 ]]> 100 0

[0078] Ratio A DRX / A 总计 is the area of ​​the peak due to the DRX structure in X-ray diffraction analysis using CuKα radiation (A DRX ) and the total area of ​​all peaks (A 总计 )

[0079] Ratio A 尖晶石 / A 总计 is the area of ​​the peak due to the spinel structure shown in the X-ray diffraction analysis using CuKα radiation (A 尖晶石 ) and the total area of ​​all peaks (A 总计 )

[0080] As listed in Table 1, in the positive electrode active material according to the present disclosure, the area (A 尖晶石 ) and the total area of ​​all peaks (A 总计 ) ratio (A 尖晶石 / A 总计 ) may be in the range of 0.1 to 99.8. In addition, in the positive active material according to the present disclosure, the area of ​​the peak due to the DRX structure presented in the X-ray diffraction analysis using CuKα radiation (A DRX ) and the total area of ​​all peaks (A 总计 ) ratio (A DRX / A 总计 ) may be a ratio of 0.2 to 0.99. Therefore, it can be confirmed that the positive electrode active material according to the present disclosure has a multi-phase structure.

[0081] Figure 8 Capacity and cycle life evaluation of a lithium secondary battery using the positive electrode active material according to Example 1 are shown. Fig. 9 Capacity and cycle life evaluation of a lithium secondary battery using the positive electrode active material according to Example 2 are shown. Fig.10 Capacity and cycle life evaluation of a lithium secondary battery using the positive electrode active material according to Example 3 are shown. Fig.11 Capacity and cycle life evaluation of a lithium secondary battery using the positive electrode active material according to Example 4 are shown.

[0082] The initial capacity and capacity retention rate of each lithium secondary battery are listed in Table 2 below.

[0083] Table 2

[0084]

[0085] refer to Figure 8-11 According to Table 2, the lithium secondary battery according to Example 1 has a high initial capacity, and the lithium secondary battery according to Example 4 has an excellent capacity retention rate. 1.25 Mn 2 O 4 The lithium secondary battery showed the best results.

[0086] As is apparent from the above description, the present disclosure provides a positive electrode active material for a lithium secondary battery having a multi-phase structure and provides a method for manufacturing the same.

[0087] In addition, the present disclosure provides a lithium secondary battery having improved energy density and cycle life.

[0088] The present disclosure has been described in detail with reference to its specific embodiments. However, it should be understood by those skilled in the art that changes may be made in these embodiments without departing from the principles and spirit of the present disclosure, the scope of which is defined in the appended claims and their equivalents.

Claims

1. A positive electrode active material for a lithium secondary battery, the positive electrode active material comprising: Lithium oxide, which has the chemical formula Li 1+x Mn2O4, where x satisfies the relationship 0≤x≤0.75, And the positive electrode active material has a multi-phase structure including at least a cationic disordered rock salt DRX structure. 2 . The positive electrode active material according to claim 1 , wherein the positive electrode active material further comprises at least one of a layered structure or a spinel structure.

3. The positive electrode active material according to claim 2, wherein the positive electrode active material exhibits peaks at 2θ=19°±0.5°, 31°±0.5°, 36.5°±0.5°, 48.5°±0.5°, 55°±0.5°, 58.5°±0.5°, 67.5°±0.5°, 68.5°±0.5°, 76°±0.5° and 84°±0.5° in X-ray diffraction analysis using CuKα radiation. 4 . The cathode active material according to claim 1 , wherein the cathode active material exhibits peaks at 2θ=38°±0.5°, 44.5°±0.5°, 64.5°±0.5°, 77.5°±0.5°, and 81°±0.5° in X-ray diffraction analysis using CuKα radiation.

5. The positive electrode active material according to claim 2, wherein the area A of the peak due to the spinel structure exhibited in X-ray diffraction analysis using CuKα radiation is 尖晶石 The total area of ​​all peaks of the positive electrode active material is A 总计 Ratio A 尖晶石 / A 总计 In the range of 0.1 to 99.

8.

6. The positive electrode active material according to claim 1, wherein the area A of the peak due to the DRX structure presented in X-ray diffraction analysis using CuKα radiation is DRX The total area of ​​all peaks of the positive electrode active material is A 总计 Ratio A DRX / A 总计 In the range of 0.2 to 0.

99.

7. The positive electrode active material according to claim 1, wherein the lithium oxide comprises Li 1.25 Mn2O4.

8. The positive electrode active material according to claim 2, wherein the area A of the peak due to the spinel structure exhibited in X-ray diffraction analysis using CuKα radiation is 尖晶石 The total area of ​​all peaks of the positive electrode active material is A 总计 Ratio A 尖晶石 / A 总计 It is 0.4 to 0.

6.

9. The positive electrode active material according to claim 1, wherein the area A of the peak due to the DRX structure presented in X-ray diffraction analysis using CuKα radiation is DRX The total area of ​​all peaks of the positive electrode active material is A 总计 Ratio A DRX / A 总计 In the range of 0.4 to 0.

6.

10. A method for manufacturing a positive electrode active material for a lithium secondary battery, wherein the positive electrode active material has a multiphase structure including at least a cationic disordered rock salt DRX structure, the manufacturing method comprising: preparing raw materials; Obtaining an intermediate material by crushing the raw material; and By heat treating the intermediate material, a Li 1+x Lithium oxide of Mn2O4, Where x satisfies the relationship 0≤x≤0.

75. 11 . The production method according to claim 10 , wherein in the step of obtaining the intermediate substance, the raw material is pulverized by applying a force in the range of 10 G to 20 G to the raw material for 10 to 30 hours using a ball mill. 12 . The manufacturing method according to claim 10 , wherein the positive electrode active material further comprises at least one of a layered structure or a spinel structure.

13. The manufacturing method according to claim 12, wherein the positive electrode active material shows peaks at 2θ=19°±0.5°, 31°±0.5°, 36.5°±0.5°, 48.5°±0.5°, 55°±0.5°, 58.5°±0.5°, 67.5°±0.5°, 68.5°±0.5°, 76°±0.5° and 84°±0.5° in X-ray diffraction analysis using CuKα radiation. 14 . The manufacturing method according to claim 10 , wherein the positive electrode active material exhibits peaks at 2θ=38°±0.5°, 44.5°±0.5°, 64.5°±0.5°, 77.5°±0.5°, and 81°±0.5° in X-ray diffraction analysis using CuK α radiation.

15. The manufacturing method according to claim 12, wherein the area A of the peak due to the spinel structure presented in X-ray diffraction analysis using CuKα radiation is 尖晶石 The total area of ​​all peaks of the positive electrode active material is A 总计 Ratio A 尖晶石 / A 总计 In the range of 0.1 to 99.

8.

16. The manufacturing method according to claim 10, wherein the area A of the peak due to the DRX structure presented in X-ray diffraction analysis using CuKα radiation is DRX The total area of ​​all peaks of the positive electrode active material is A 总计 Ratio A DRX / A 总计 In the range of 0.2 to 0.

99.

17. The manufacturing method according to claim 10, wherein the lithium oxide comprises Li 1.25 Mn2O4.

18. The manufacturing method according to claim 12, wherein the area A of the peak due to the spinel structure exhibited in X-ray diffraction analysis using CuKα radiation is 尖晶石 The total area of ​​all peaks of the positive electrode active material is A 总计 Ratio A 尖晶石 / A 总计 In the range of 0.4 to 0.

6.

19. The manufacturing method according to claim 10, wherein the area A of the peak due to the DRX structure presented in X-ray diffraction analysis using CuKα radiation is DRX The total area of ​​all peaks of the positive electrode active material is A 总计 Ratio A DRX / A 总计 In the range of 0.4 to 0.6.